Dynamic Lateral Stability Analysis On Pipeline Under Operating Conditions - Soni Fachryan Akbar; Yeyes Mulyadi; Nur Syahroni (Department of Ocean Engineering, 2025)
The stability analysis of underwater pipelines refers to DNVGL RP F109 [3] (On-bottom Stability Design of Submarine Pipelines) and DNVGL RP F114 [2] (Pipe Soil Interaction) from 2017. The selection of analysis methods depends on the required level of detail in the design analysis. Dynamic analysis introduces more complexity in terms of numerical calculations and field conditions. It involves simulating the pipe's response to hydrodynamic loads, including random waves, steady currents, and soil resistance in the time domain to replicate extreme conditions realistically. The study's outcomes demonstrate that hydrodynamic forces analyzed through numerical methods in CFD software can be compared to analytical approaches outlined in DNV GL F109 and F114 with an error margin of less than 10%. The Maximum Lateral Displacement is measured at 86.49 mm, falling within the allowable displacement range of 0.5 – 10 times the pipe's outer diameter, as specified in DNV GL F109 & DNVGL F114 guidelines. The Von Mises Stress along the pipeline reaches 266.18 MPa, satisfying the 90% SMYS criteria stipulated in ASME B31.8 [2]